Evaluation of Skeletal Changes after Mandibular Setback Surgery Using the NM-Low Z Plasty Technique in Skeletal Class III Patients - Imampai, Sarunpong; Patchanee, Siripatra; Klaisiri, Awiruth; Chaiprakit, Narissaporn (European Journal of Dentistry, 2022)
Objective The study's objective was to evaluate skeletal changes in 38 skeletal class III patients following mandibular setback surgery using NM-Low Z plasty.Materials and Methods Thirty-eight skeletal class III patients (ANB angle lower than 0) who underwent the NM-Low Z plasty technique for surgical mandibular setback procedure at Thammasat University Hospital between January 2017 and March 2020 were included in the study: 29 patients had two jaw surgeries, and 9 patients had one jaw surgery. An additional 14 patients had genioplasty. Three lateral cephalograms were traced and digitized with Dolphin Imaging software: T0, T1, and T2. The distance between the B-point and the SN7 perpendicular line defined immediate changes after surgery (T1-T0) and stability after surgery (T2-T1). The reliability test included 6 cephalograms retraced after 2-week interval. At point B, the principal result was horizontal movement forward.Statistical Analysis The analysis used paired t-tests.Results The mean mandibular setback was 9.78 mm, and the mean skeletal relapse was 2.61 mm, or 26.69%. Statistical analysis showed postoperative differences (p < 0.05). Vertical measurement in B-SN7 reduced immediately and postoperatively.Conclusion Postoperatively, the mandible relapsed significantly forward and upward. Rotational relapse is a concern with NM-Low Z plasty in hypo-/normodivergent patients.
Keywords: malocclusion; mandibular setback; orthodontics; orthognathic surgery; skeletal class III; skeletal relapse